Monitoring and Assessing Cardiac Patients’ Knowledge and Adherence Pre-Discharge Post-PCI - Fayez Al-Zubair; Mansour Al Moudi; Aymen Al-Husaini; Lina Al Dakil; Mubarak Al-Dossari (Dr. Sulaiman Al Habib Medical Journal)
Objective: This study aimed to Previous follow-up of patients in the outpatient clinics of the Heart Health Center at King Saud Medical City, the Kingdom of Saudi Arabia, has shown that many patients did not have a good understanding of their cardiovascular disease diagnosis, the medical procedure that was used to treat them, and the importance of adhering to patient actions required by the prescribed treatments. Aims: To identify the reasons for patients’ noncompliance with their prescribed medication regimens after undergoing cardiac stent placement. Setting and Design: This study was conducted on 235 patients who had undergone percutaneous cardiac intervention and stent implantation at the Heart Health Center of King Saud Medical City between August and October 2023. Methods and Materials: The random sampling method was used to recruit the participants before they were discharged from the hospital. The average participant age was 54 years, and 87% were male. Statistical Analysis: A standardized questionnaire was used to gather analytical information. Descriptive and inferential statistics were used for data analysis. Result: Approximately 36.2% of the participants were covered by the medical insurance program, whereas approximately two-thirds of non-Saudi patients (63.8%) were not covered, which negatively affected the patients’ compliance with taking treatments in the required period. Moreover, 12% of the patients did not know exactly how long it would take to complete their treatment, and 73% of them were not directed to alternative resources in this field, such as specialized charitable organizations. Furthermore, a difference in treatment knowledge was observed between the male and female participants, with only 1% of the male participants not knowing the importance of the treatment prescribed to them and the danger of stopping it, whereas 14.8% of the female participants were unaware. Conclusion: The majority of the Saudi and non-Saudi patients had at least the required knowledge about the diagnosis of their disease, the medical procedure they underwent, and the importance of complying with the prescribed treatment regimen. Additionally, they were satisfied with the level of medical service provided to them.